Becoming an LGBTQ+ storyteller: Collecting and using data on gender, sex, and sexual orientation. Issue 175 (21st October 2022) - Felt, Dylan; Perez‐Bill, Esrea; Ruprecht, Megan M.; Petillo, Michael; Beach, Lauren B.; Glenn, Erik Elías; Phillips, Gregory
Abstract: LGBTQ+ stories and histories have long been silenced as part of deliberate work by those in power to erase our identities and experiences. As evaluators, we contribute to the process of either silencing or uplifting LGBTQ+ stories. This aspect of our work begs a number of vital questions that each of us must reckon with when we approach an evaluation: What data are necessary to allow us to tell a story? What story will we tell with the data we have collected? And, most importantly, who does the telling of certain stories benefit, who might it harm, and what is our responsibility as evaluators to protect peoples' stories? Proceeding from these questions, this chapter has three distinct parts. In Part One, we establish a common language. By integrating perspectives from the social sciences and LGBTQ+ community scholarship, we provide an overview of the complex and contextually specific nature of sex, sexual orientation, and gender, and discuss the implications of these complexities on how we approach collecting LGBTQ+ data. In Part Two, we consider the power of the stories we tell to impact the lives of LGBTQ+ people, and the frameworks, theories, and ethical imperatives which may help us to contribute to a narrative of LGBTQ+ liberation through our work. Finally, in Part Three, we offer an example tool for readers to use as they consider how they would approach this work in their own practices.